Introduction and evaluation of Phymastichus coffea (Hymenoptera: Eulophidae) in smallholder coffee farrns. through participatory research - ARISTIZÁBAL-A., LUIS FERNANDO; SALAZAR-E., HUGO MAURICIO; MEJÍA-M., CARLOS GONZALO; BUSTILLO-P., ALEX E. (Revista Colombiana de Entomología, 2004)
In collaboration with ICO-CFC-CABI Bioscience, Cenicafé conducted a farmer parlicipatory research project with smallholder coffee growers in Caldas, Quindío and Risaralda, related to the management of the coffee berry borer. During this study the flrst release of Phymastichus coffea (La Salle) was made in Colombia with the main purpose of allowing farmers to learn about this parasitoid, initiate its introduction, and evaluate its establishment. Forty-one coffee farms participated in the study. which were located between 1.200 and 1.800 meters elevation. For 20 months coffee berry borer management was based on frequent harvests of mature coffee and releases of P. coffea. Farmers made evaluations of insect infestation, positions of borer penetration in the berry and collected infested berries to evaluate the parasitoid establishment. Altogether 455 samples of infested berries were collected. In 49,2% (N = 224) of the samples the presence of P. coffea was observed. The presence of P. coffea was detected up to 14 months after the last release. In farms of Balboa, Montenegro and Belalcázar, the highest parasitism was observed: mean of 5,6, 5,6 and 4. 7%, respectively. In contrast. farms of Riosucio, Buenavista and Santa Rosa de Cabal, had lower parasitism: mean of O, 7, 1,3 and 1,9%, respectively. Maximum parasitism observed was 42%. lt is important to emphasize that P. coffea was present in 87,5 % of the farms where it was released. demonstrating that it can be established in the coffee agroecosystems of the country.